Influence of the First Wave of the COVID-19 Pandemic on Cancer Care in a German Comprehensive Cancer Center - Kirchberg, Johanna; Rentsch, Anke; Klimova, Anna; Vovk, Vasyl; Hempel, Sebastian; Folprecht, Gunnar; Krause, Mechthild; Plodeck, Verena; Welsch, Thilo; Weitz, Jürgen; Fritzmann, Johannes (Frontiers in Public Health, 2021)
Introduction: During the first wave of the COVID-19 pandemic in 2020, the German government implemented legal restrictions to avoid the overloading of intensive care units by patients with COVID-19. The influence of these effects on diagnosis and treatment of cancer in Germany is largely unknown. Methods: To evaluate the effect of the first wave of the COVID-19 pandemic on tumor board presentations in a high-volume tertiary referral center (the German Comprehensive Cancer Center NCT/UCC Dresden), we compared the number of presentations of gastrointestinal tumors stratified by tumor entity, tumor stage, and treatment intention during the pandemic to the respective data from previous years. Results: The number of presentations decreased by 3.2% (95% CI −8.8, 2.7) during the COVID year 2020 compared with the pre-COVID year 2019. During the first shutdown, March–May 2020, the total number of presentations was 9.4% (−18.7, 1) less than during March–May 2019. This decrease was significant for curable cases of esophageal cancer [N = 37, 25.5% (−41.8, −4.4)] and colon cancer [N = 36, 17.5% (−32.6, 1.1)] as well as for all cases of biliary tract cancer [N = 26, 50% (−69.9, −15)] during the first shutdown from March 2020 to May 2020. Conclusion: The impact of the COVID-19 pandemic on the presentation of oncological patients in a CCC in Germany was considerable and should be taken into account when making decisions regarding future pandemics.